Systematic review of maternal Placental Growth Factor levels in late pregnancy as a predictor of adverse intrapartum and perinatal outcomes. (June 2018) - Sherrell, Helen; Dunn, Liam; Clifton, Vicki; Kumar, Sailesh
Abstract: Aim: This systematic review evaluates the utility of maternal Placental Growth Factor (PlGF) when measured in late pregnancy (>20 weeks) as a predictor of adverse obstetric and perinatal outcomes. Methods: Pubmed and Embase were searched using the term "placental growth factor" in combination with relevant perinatal outcomes. Studies were included if they measured PlGF levels in pregnant women after 20 + 0 weeks gestation and reported relevant adverse obstetric or perinatal outcomes related to placental insufficiency (excluding pre-eclampsia). Results: Twenty-six studies were eligible for inclusion with 21 studies investigating the relationship between PlGF and small for gestational age (SGA) and 7 studies investigating PlGF for the prediction of other adverse perinatal outcomes. In all studies, maternal PlGF levels were significantly lower in the SGA group compared to controls. Other outcomes investigated included caesarean section (CS) for fetal compromise, low Apgar score, neonatal intensive care unit (NICU) admission, neonatal acidosis, stillbirth, and intrapartum fetal compromise. The results generally showed a significant association between low PlGF levels and CS for fetal compromise, NICU admission and stillbirth. Conclusion: Low maternal PlGF levels in late pregnancy are strongly associated with SGA. Findings across studies were variable in relation to PlGF and the prediction of other adverse intrapartum and perinatal outcomes, however there was a consistent association between low PlGF levels and CS for fetal compromise, NICU admission and stillbirth. This review suggests that the use of PlGF for the prediction of adverse outcomes is promising. Its predictive value may potentially be enhanced if used in combination with other biomarkers or biophysical measures of fetal well-being.